Effect of the Use of Reinforced Stapling on the Occurrence of Pancreatic Fistula After Distal Pancreatectomy: Results of the REPLAY (REinforcement of the Pancreas in distaL pAncreatectomY) Multicenter Randomized Clinical Trial. Issue 5 (25th November 2022) - Merdrignac, Aude; Garnier, Jonathan; Dokmak, Safi; Regenet, Nicolas; Lesurtel, Mickaël; Mabrut, Jean Yves; Sa Cunha, Antonio; Fuks, David; Bergeat, Damien; Robin, Fabien; Le Pabic, Estelle; Boudjema, Karim; et al.
Abstract : Objective: The aim of the study was to evaluate the impact of the use of a reinforced stapler (RS) during distal pancreatectomy (DP) on postoperative outcomes. Background: DP remains associated with significant postoperative morbidity owing to pancreatic fistula (PF). To date, there is no consensus on the management of the pancreatic stump. The use of an RS potentially represents a simple way to decrease the rate of PF. Methods: The REPLAY study (NCT03030170) is a prospective, multicenter, randomized study. Patients who underwent DP were randomized (1:1 ratio) in 2 groups for the use of a standard stapler (SS) or an RS to close remnant pancreatic parenchyma. The primary endpoint was the rate of overall PF. Secondary endpoints included severity of PF, length of hospital stay, overall morbidity, and rate of readmission for a PF within 90 days. Participants were blinded to the procedure actually carried out. Results: A total of 199 were analyzed (SS, n=99; RS, n=100). One patient who did not undergo surgery was excluded. Baseline characteristics were comparable in both groups. The rate of overall PF was higher in RS group (SS: 67.7%, RS: 83%, P =0.0121), but the rate of clinically relevant PF was similar (SS: 11.1%, RS: 14%, P =0.5387). Mean length of total hospital stay, readmission for PF, postoperative morbidity, and mortality at 90 days were similar. Conclusion: The results of this randomized clinical trial did not favor the use of RS during DP to reduce the rate of PF.